The consequences of poor specification and standardization in public organizations: A case study of Kibaha education centre - Josephat, Jones (2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the degree of Master of Science in Procurement and Supply Chain Management (Msc - PSCM) of Mzumbe University.